Harsh physical punishment as a mediator between income, re-reports and out-of-home placement in a child protective services-involved population. (August 2019) - Feely, Megan; Seay, Kristen D.; Loomis, Alysse M.
Abstract: Poverty is consistently associated with a higher risk of experiencing child maltreatment, and children from poor families are the majority of children involved in child protective services (CPS). However, the mediators in the relationship from income to CPS involvement are not entirely understood. Using theoretically-informed mediating path models and data from the second National Survey of Child and Adolescent Well-Being (NSCAW II), this study tests the role of harsh physical punishment as a mediator between family income and CPS involvement. CPS involvement was measured by subsequent report of maltreatment and removal to out-of-home care. The direct paths from income to re-report and to removal were significant; with higher income associated with lower risk of report and removal. Lower income was significantly associated with higher rates of harsh physical punishment. However, harsh punishment did not mediate the relationship between income and the outcomes. These results suggest that even within a population primarily comprised of low-income families, lower income is a risk for subsequent reports and removals as well as a risk for higher rates of harsh physical punishment. However, in this sample harsh physical punishment is not the mechanism that results in higher subsequent-reports or removal rates. Highlights: Tested harsh physical punishment as mediator between family income and CPS outcomes. Lower income was significantly associated with higher harsh physical punishment. Harsh punishment did not mediate between income and CPS outcomes. Direct path from family income to re-report of maltreatment was significant. Direct path from family income to removal to out-of-home care was significant.